Hallazgo de radiolarios del Paleógeno en la Isla Grande de Tierra del Fuego, Argentina - Jannou, Gabriel Eugenio; Olivero, Eduardo Bernardo
The finding of two assemblages of well preserved radiolarians, one from Punta Gruesa and the other from Cabo Irigoyen-Arrayo Vasco area, on the Atlantic coast, Tierra del Fuego Island, is reported. The former contains: Amphicraspedum sp. d. A. murrayanum Haeckel, Buryella dumitricai (Petrushevskaya), Orbiculiforma renillaeformis (Campbell and Clark), and Corythomelissa adunca (Sanfilippo and Riedel) among the most representantive species, its age is constrained to Late Paleocene-Early Eocene. The latter assemblage contains Theocotyle (Theocotylissa) ficus (Ehrenberg), Amphisphaera macrosphaera (Nishimura), Buryella tetradica Foreman, and Spcngurus bilobatus Clark and Campbell, its age is Early Eocene in agreement with the associated planktonic foraminifera. Both assemblages contain Heliostylus sp., Mita sp., and Stylosphaera minor Clark and Campbell. Fil: Jannou, Gabriel Eugenio. Secretaría de Industria y Minería. Servicio Geológico Minero Argentino; Argentina Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina